PENGELOLAAN KOLEKSI MUSEUM ZOOLOGICUM BOGORIENSE (MZB) TAHUN 2022 - Mujiono, Nova; Alfiah, Alfiah; Apandi, Apandi; Darmawan, Darmawan; Fatimah, Fatimah; Wikanta, Hadi; Haerul, Haerul; Kurnianingsih, Kurnianingsih; Wahyudin, Mohamad; Mulyadi, Mulyadi; Supriatna, Nanang; Santoso, Pramono Hery; Prihandini, Riena; Rachmatiyah, Rina; Sarino, Sarino; Sauri, Sopian; Suparno, Suparno; Nurhaman, Ujang; Sofyani, Umar; Trilaksono, Wahyu; Priyatna, Yayat (Berita Biologi, 2024)
Since the integration of LIPI into BRIN in 2021, the Museum Zoologicum Bogoriense (MZB), which is managed by the coordinator of the zoological collection assisted by 20 collection technician staffs, has been transferred to the Directorate of Scientific Collections Management. The process of integration and management transfer does not change the main duties and functions of MZB as the national depository for zoological specimen collections. In addition to managing collections, researchers frequently ask MZB staff for assistance during field research and teaching collection management courses to students, teaching staff, and regional museum directors. The management of the MZB collection is described in a scientific publication for the first time. We hope that this documentation will continue so that museum management science can advance and assist the scientific community, particularly in Indonesia.